PROFIL LANJUT USIA DENGAN DEPRESI YANG TINGGAL DI BALAI PENYANTUNAN LANJUT USIA SENJA CERAH MANADO - Ballo, Ivone R; Kaunang, Theresia M D; Munayang, Herdy; Elim, Christoffel (UNIVERSITAS SAM RATULANGI, 2012)
Abstract: According to the World Health Organisation, depression is still a serious public health problem. Depression is a mood disorder due to a disturbance in human functions related to sad feelings that can occur in every individual, including the elderly. The purpose of this study was to find out the profile of the elderly living in BPLU Senja Cerah (Senior Citizens Home) Manado who suffered from depression. This was an observational study with a cross-sectional design. Samples were all elderly, living in the BPLU Senja Cerah that were willing and able to become respondents, and fulfiled the inclusive and exclusive criteria, including signing informed consents and not suffering from any chronic diseases, such as strokes or cardiac diseases. The study showed that depression was mostly found at the ages of 61-74 years (25%) and after 1-6 months of staying in BPLU Senja Cerah (21.3%); the occurence of depression was higher in females (29.8% of total respondents); and the most frequent type was mild depression (30.4%). Conclusion: in BPLU Senja Cerah Manado, the respondents who most suffered from depression were in the following categories: the ages of 61-74 years, females, mild types of depression, and having stayed 1-6 months at the center. Keywords: depression, elderly, prevalence of depressionÂ Â Abstrak: World Health Organization (WHO) mengemukakan bahwa depresi masih merupakan masalah kesehatan masyarakat yang serius. Depresi adalah gangguan mood dimana terganggunya fungsi manusia berkaitan dengan alam dan perasaan yang sedih. Gangguan depresi dapat terjadi pada semua individu, termasuk lanjut usia. Penelitian ini bertujuan untuk mengetahui prevalensi gangguan depresi pada lanjut usia yang tinggal di Balai Penyatunan Lanjut Usia (BPLU) Senja Cerah Manado. Penelitian ini menggunakan jenis penelitian observasi dengan deain potong lintang. Sampel penelitian ialah semua lanjut usia yang tinggal di BPLU Senja Cerah Manado yang memenuhi kriteria inklusi dan eksklusi, antara lain bersedia dan bisa menjadi responden serta menandatangani informed consent, dan tidak menderita penyakit kronik seperti stroke atau gangguan jantung. Depresi paling banyak dialami pada kelompok umur 61-74 tahun (25,5%), telah berdiam di BPLU Senja Cerah selama 1-6 bulan (21,3%), berjenis kelamin perempuan (29,8%), dengan tingkat depresi ringan yang terbanyak (30,4%). Simpulan: pada lanjut usia yang tinggal di Balai Penyatunan Lanjut Usia (BPLU) Senja Cerah Manado depresi ditemukan terbanyak pada usia 61-74 tahun, jenis kelamin perempuan, jenis depresi ringan, dengan masa tinggal 1-6 bulan. Kata kunci : Depresi, lanjut usia, prevalensi depresi